Foreignization Strategy in the Quranic Translation by MoRA: Study of Surah Al-Baqarah - Toto Edidarmo; Zainal Muttaqin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study aims to find out in-depth about the application of foreignization strategies in translating the Quran into Indonesian. The application of foreignization strategies in terms of meaning accuracy in the source language (SL) and target language (TL) as well as its suitability with the cultural context. The research method used is content analysis adapted from Krippendorff (1980). Based on an analysis of the foreignization strategy implemented by the Quran Translation Team of the Ministry of Religious Affairs (MoRA) of the Republic of Indonesia, it was found that 94 words and phrases were foreignized in the translation of Surah Al-Baqarah. Judging from the aspect of the accuracy of meaning, equivalence, and its use in Indonesian, the vocabulary is still accurate in meaning, as intended by the SL text and its users. However, some absorption vocabularies experience a shift in meaning, broad, narrow, general, and specific, as well as those containing good and bad values. Two factors influence the translator in implementing the foreignization strategy in the translation of the Quran, namely (a) the condition of the Quranic text, which is difficult to translate into Indonesian, and (b) the translator’s belief that foreign vocabulary retention (foreignization) can give the nuances of the authenticity of Arabic culture (Quran).